A3.26 Proteasome inhibition with bortezomib in refractory SLE inhibits type I interferon and depletes plasma cells but does not inhibit their regeneration. (31st January 2014) - Alexander, Tobias; Cheng, Qingyu; Klotsche, Jens; Hoyer, Bimba; Taddeo, Adriano; Waka, Aderajew; Kühl, Anja A; Burmester, Gerd-Rüdiger; Radbruch, Andreas; Hiepe, Falk
Abstract : Background: The proteasome inhibitor bortezomib, approved for the treatment of multiple myeloma, has been demonstrated to deplete short- and long-lived plasma cells (PCs) and ameliorate nephritis in murine models of systemic lupus erythematosus (SLE). Here, we aimed to analyse the effect of bortezomib in refractory SLE patients. Methods: In this single-centre cohort study, eight SLE patients with active disease despite immunosuppressive treatment received up to four 21-day cycles of bortezomib 1.3mg/m 2, on days 1, 4, 8, and 11 by intravenous injection as an "off-label" treatment. Multicolor flow cytometry was performed to analyse peripheral blood B and PC subsets as well as Siglec-1 expression on monocytes. Autoantibody and vaccine titres as well as B cell activating factor (BAFF) levels in serum were analysed with ELISA. Results: From 2009 until 2012, eight SLE patients received a median of two bortezomib cycles (range one to four). Under proteasome inhibition, disease activity significantly improved with a median SLEDAI reduction from 13 to 4 (p>0.001). Bortezomib treatment had profound effects on antibody titers, with greater reduction in pathogenic (anti-dsDNA-abs. 58.7%) than protective antibody titers (e.g. anti-Tetanus-abs. 29.2%). In addition, total immunoglobulin levels and Siglec-1 expression on monocytes (as surrogate for type I interferon) significantly decreased (p = 0.016), whereas BAFF and complement levels significantly increased. While circulating B-cell numbers remained unaffected, bortezomib treatment resulted in a significant depletion of both HLA-DR + short-lived (55.5% reduction, p = 0.024) and HLA-DR- long-lived (53.5% reduction, p = 0.038) peripheral blood PCs. Also IgA secreting PCs were depleted (61.8% reduction). Nevertheless, PCs were rapidly regenerated with a median increase of 268.8% within 10 days from the last bortezomib application. Conclusion: Proteasome inhibition with bortezomib has beneficial effects on disease manifestations in SLE by PC depletion and inhibition of type I interferon but regeneration of PCs is not prevented. Overall, proteasome inhibition has demonstrated the therapeutic relevance of targeting autoreactive memory plasma cells as such, and it constitutes a new therapeutic option. Nevertheless, fur sustained efficacy, proteasome inhibition needs to be combined with therapeutic approaches targeting B cell activation and differentiation to inhibit PC regeneration.